Alternative Counselling Interventions in Improving Self-Esteem of Students' Subjective Well Being: A Literature Review - Risky Kurnia Perdana; Agus Basuki; Intan Prawitasari (STAI Hubbulwathan Duri, 2022)
The implementation of educational activities involved a learning process including knowledge and skills with developing student character. However, in the learning process, there are some problems occur. The problems were usually related to the negative attitudes and traits shown by students. The negative attitudes and traits shown by students are caused by low self-esteem. The purpose of this study was to describe the alternative counselling interventions through Guidance and Counseling, Rational Emotive Behavior Therapy (REBT) to increase students' self-esteem and to show the effect of self-esteem on students' subjective well-being. This research used a qualitative approach. The data analysis technique used is qualitative data analysis, where the data comes from the study of literature assertive training, cognitive, behavioural, and modelling. The result of this study is self-esteem and subjective well-being can improve by Rational Emotive Behavior Therapy or REBT.